2019
DOI: 10.15282/jmes.13.1.2019.01.0371
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization and optimization of heat treatment parameters of manganese alloyed austempered ductile iron

Abstract: Austempered Ductile Iron (ADI) belongs to the family of cast irons whose mechanical properties are altered using austempering heat treatment process. The objective of this paper is to study the effects of heat treatment parameters on manganese alloyed ADI. Hence, austenitization temperature, austempering temperature and austempering time are taken as the control variables along with the manganese content in the material. The effects of heat treatment are studied by measuring the ultimate tensile strength and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This may be because of the higher amount of retained austenite obtained at this austempering temperature (Olawale & Oluwasegun, 2016). The ultimate tensile strength data is taken from the previously reported results from the same project by the same author (Hegde et al, 2019) for the comparison purpose. It may be seen that tensile strength obtained at the higher austempering temperature of 420°C is lower because of the coarser structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be because of the higher amount of retained austenite obtained at this austempering temperature (Olawale & Oluwasegun, 2016). The ultimate tensile strength data is taken from the previously reported results from the same project by the same author (Hegde et al, 2019) for the comparison purpose. It may be seen that tensile strength obtained at the higher austempering temperature of 420°C is lower because of the coarser structure.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analysis is carried out to fit the regression model so that impact energy may be predicted for various austempering temperature. In the earlier study of the same project, it is reported about the tensile strength of ADI at various condition (Hegde et al, 2019). In the current study, with the additional results of impact energy and ductility, manganese content and austempering temperature are optimized in order to obtain superior combination of tensile strength and impact energy.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This justifies the variation in mechanical properties with the change in heat treatment parameters. Hardness and tensile strength values have been found to be decreasing with increasing austempering temperature [17][18][19] . These reduction in hardness and strength may be attributed to the coarser grains obtained at higher austempering temperature.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Amount of retained austenite has increased with the increase in the austempering temperature from 320 to 420ºC. This resulted in the lower hardness at the higher austempering temperature of 420ºC 17 .…”
Section: Microstructure Analysismentioning
confidence: 99%